The Language Of Consciousness: A Literary Exploration Of Metaphor In Mrs. Dalloway By Virginia Woolf’ - Komandari, Carmen Syarifah Meihwa; Parthama, I Gusti Ngurah; Puspitaning Adni, Nissa (Jurnal Ilmiah Wahana Pendidikan, 2026)
Metaphors play an important function in literature since they serve to convey complicated psychological and emotional experiences in a more accessible and imaginative manner. This article investigates the use of metaphor in Virginia Woolf's psychological book Mrs. Dalloway (1925), identifying several metaphor types and revealing their underlying meaning. This study uses a qualitative descriptive method and Ritchie's (2013) framework to categorize and understand metaphors in the novel. The findings suggest that metaphorical terms are useful in depicting the characters' interior sensations. The analysis reveals how metaphor enhances the emotional resonance and psychological realism of the tale through a close reading of selected excerpts.